2022
DOI: 10.1039/d2cc00258b
|View full text |Cite
|
Sign up to set email alerts
|

Twofold rattling mode-induced ultralow thermal conductivity in vacancy-ordered double perovskite Cs2SnI6

Abstract: Here, we report a first-principles study of lattice vibrations and thermal transport in Cs2SnI6, the archetypal compound in the family of vacancy-ordered double perovskites. We show that twofold rattlers of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…The anharmonic rattling dynamics of Cs atoms are also found in Cs-containing vacancyordered double perovskites. [41][42][43] It can also be seen that the hardening of the phonon frequencies of rattling modes is significant, especially for acoustic modes at the zone boundary and low-frequency optical modes around the zone center. This obvious phonon renormalization indicates strong anharmonicity, which can severely suppress phonon transport.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The anharmonic rattling dynamics of Cs atoms are also found in Cs-containing vacancyordered double perovskites. [41][42][43] It can also be seen that the hardening of the phonon frequencies of rattling modes is significant, especially for acoustic modes at the zone boundary and low-frequency optical modes around the zone center. This obvious phonon renormalization indicates strong anharmonicity, which can severely suppress phonon transport.…”
Section: Resultsmentioning
confidence: 97%
“…The anharmonic rattling dynamics of Cs atoms are also found in Cs-containing vacancy-ordered double perovskites. 41–43…”
Section: Resultsmentioning
confidence: 99%
“…From the phonon dispersion spectrum (Figure ), it can be found that at T = 0 K, there are soft modes with negative frequencies (at gamma and other symmetry points of the BZ) for all the understudy compounds, which shows that the In 2 PtX 6 perovskites are dynamically unstable. The major cause of the soft phonon modes in the In 2 PtX 6 structure is the two-fold rattling of the In and PtX 6 octahedral cluster . However, at T = 300 K, no imaginary frequencies appear in the whole BZ, demonstrating the dynamical stability of In 2 PtX 6 at high temperatures.…”
Section: Resultsmentioning
confidence: 96%
“…The major cause of the soft phonon modes in the In 2 PtX 6 structure is the twofold rattling of the In and PtX 6 octahedral cluster. 34 However, at T = 300 K, no imaginary frequencies appear in the whole BZ, demonstrating the dynamical stability of In 2 PtX 6 at high temperatures. Our results are consistent with a recently published work and suggest that the studied compounds are likely to be synthesized in experiments.…”
Section: Methodsmentioning
confidence: 91%
“…For instance, benefiting from large absorption coefficients, high charge carrier mobility, and long carrier diffusion lengths, HPs have been recognized as promising photovoltaic materials and further applied in various optoelectronic devicesLEDs, lasers, photodetectors, and X-ray detectors . In addition to optoelectronic applications, the cubic perovskite structure of HPs leads to ferroelectric polarization, which is applied in piezoelectric energy harvesting devices. , Just recently, the potential room-temperature thermoelectric (TE) application of HPs has attracted wide attention due to their intrinsic ultralow lattice thermal conductivity originating from the cluster rattling mechanism. …”
Section: Introductionmentioning
confidence: 99%